(untitled) (Konferensiyalar | Conferences, 2024)
In recent years, many studies have begun to appear in world psychology and linguistics on issues of the psyche, language, and speech activity. Because the bulk of information reaches human consciousness through the linguistic direction. The article psycholinguistics the sphere of human education psychology and tiling are the foundations of personality psychology. Also, errors and difficulties in learning a second language were seen as a psycholinguistic problem. And his research is expressed on the basis of scientific sources.